A Review of Feasible Applications of THz Waves in Medical Diagnostics and Treatments: Feasible Applications of THz Waves in Medicine - Amini, Tahereh; Jahangiri, Fazel; Ameri, Zoha; Hemmatian, Mohammad Amin (Journal of Lasers in Medical Sciences, 2021)
Introduction: Terahertz (THz) waves with frequencies in the range of 0.1 to 10 THz are electromagnetic radiation with growing applications in various fields of science and technology. Attractive features of this radiation have brought out many novel possibilities for medical diagnostics and treatments with considerable advantages compared to other conventional methods. Methods: In this paper, we present a review of more recent reports on practical applications of THz radiation for diagnostic, biosensing, and clinical treatments. The review includes the diagnosis of breast, skin, mouth, cervical, lungs, small intestine, prostate, colon, and stomach cancers, the evaluation of biomolecules, the detection of genetic mutations, the determination of burn depth, the diagnosis of tooth decay, diabetes, and emotional-psychological states, the evaluation of corneal water to diagnose visual diseases, and wound healing monitoring. Further, it embraces the use of THz therapy in reducing the size of the tumor, treating skin cancer, and healing burn wounds, cardiovascular disease, corneal epithelium, angina, and THz heating. Results: This review has emphasized the capabilities of THz waves as a novel tool for future clinical diagnostics and treatments. Conclusion: The paper provides a comprehensive understanding of the feasible potential application of THz waves for clinical purposes and their advantages in comparison with other conventional tools. DOI: 10.34172/jlms.2021.92